Morphological description and DNA barcoding of Thalassomya paraskevae sp. nov. (Diptera: Chironomidae: Telmatogetoninae) from coast of the Black Sea - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M.; Lisanovskaya, Elena A. (Zootaxa, 2024)
Illustrated description of adult male, as well as DNA barcoding, of Thalassomya paraskevae sp. nov. in comparison with close related species T. frauenfeldi Schiner from coast of the Black Sea are provided. Interspecific p-distances using gene COI 5P between T. paraskevae sp. nov. and T. frauenfeldi from Madeira (Portugal) were 8.94%. Divergence between described species and T. frauenfeldi collected near the type locality (Friuli Venezia-Giulia, Italy) using COI 3P were 7.72%. Obtained values corresponds to species level.